Validitas Lembar Kerja Siswa (LKS) Berbasis Discovery Learning Pada Materi Gelombang Cahaya - Ariani, Tri; Lovisia, Endang (Institut Teknologi Pendidikan Indonesia, 2023)
This study aims to develop student worksheets (LKS) based on valid discovery learning. Theresearch method used is research and development using the Dick and Carry development model. The Dick and Carey development model consists of 10 stages, namely identifying teaching objectives, conducting instructional analysis, identifying initial behavior/student characteristics, formulating performance goals, developing benchmark reference tests, developing teaching strategies, developing or selecting teaching, designing andimplementing formative evaluations, writing teaching tools and revisions. The data collection instrument in this study used a validation questionnaire, which consisted of language, media, and material validation. The type of data in this study is primary data obtained directly from the validator through testing the validity of student worksheets (LKS) based on discovery learning. The results of this research and development resulted in a discovery learning-based Student Worksheet (LKS) with a percentage value of material eligibility of 81.94% included in the very good category, media feasibility of 86.40% included in the very good category, and language feasibility of 75% in the good category.Based on the findings in this study, it can be concluded that the student worksheets (LKS)based on discovery learning are appropriate for use as learning media.